Primary hypercholesterolemia and development of cardiovascular disorders: Cellular and molecular mechanisms involved in low-grade systemic inflammation and endothelial dysfunction. (October 2021) - Collado, Aida; Domingo, Elena; Piqueras, Laura; Sanz, Maria-Jesus
Highlights: PRIMARY hypercholesterolemia (PH) is associated with arteriosclerosis development. Low-grade systemic inflammation (LGSI) is involved in premature atherosclerosis. LGSI consists in elevated inflammatory mediators and platelet/leukocyte activation. TNFα induces endothelial dysfunction through different signaling pathways. Combined lipid-lowering/anti-TNFα therapies may impair cardiovascular disease in PH. Abstract: Primary hypercholesterolemia, a metabolic disorder characterized by elevated circulating levels of cholesterol products, mainly low-density lipoproteins, is associated with arteriosclerosis development. Cardiovascular disease, predominantly myocardial infarction and stroke, remains the main cause of death worldwide, with atherosclerosis considered to be the most common underlying pathology. In addition to elevated plasma levels of low-density lipoproteins, low-grade systemic inflammation and endothelial dysfunction seem to be the main drivers of premature atherosclerosis. Here we review current knowledge related to cellular and molecular mechanisms involved in low-grade systemic inflammation and endothelial dysfunction associated with primary hypercholesterolemia. We also discuss the contribution of different inflammatory mediators, immune players and signaling pathways implicated in leukocyte adhesion to the dysfunctional endothelium, a key feature of atherogenesis development. A better understanding of these processes linked to primary hypercholesterolemia should shed new light on cardiovascular disease development and might guide novel and effective therapeutic strategies to impair its progression.